2020
DOI: 10.1007/s00253-020-10974-5
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter sp.: Pathogenicity factors and prevention methods—new molecular targets for innovative antivirulence drugs?

Abstract: Infections caused by bacterial species from the genus Campylobacter are one of the four main causes of strong diarrheal enteritis worldwide. Campylobacteriosis, a typical food-borne disease, can range from mild symptoms to fatal illness. About 550 million people worldwide suffer from campylobacteriosis and lethality is about 33 million p.a. This review summarizes the state of the current knowledge on Campylobacter with focus on its specific virulence factors. Using this knowledge, multifactorial prevention str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 218 publications
2
66
0
Order By: Relevance
“…C. jejuni is known to cause Guillain–Barré syndrome, characterized by acute and progressive neuromuscular paralysis, mediated by sialyltransferases ( cst II) ( Koga et al, 2006 ; Humphrey et al, 2007 ; González-Hein et al, 2013 ). Sialic acid confers immune avoidance to C. jejuni , as a mutant lacking lipooligosaccharide sialic acid residues showed greater immunoreactivity and decreased serum resistance ( Kreling et al, 2020 ). The CDT complex, another important factor in Campylobacter , codes for the cytolethal distending toxin with cdt B acting as the catalytic site, and in the nucleus, cdt B induces cell cycle arrest and leads to apoptosis of both immune and epithelial cells in the intestines ( Jain et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…C. jejuni is known to cause Guillain–Barré syndrome, characterized by acute and progressive neuromuscular paralysis, mediated by sialyltransferases ( cst II) ( Koga et al, 2006 ; Humphrey et al, 2007 ; González-Hein et al, 2013 ). Sialic acid confers immune avoidance to C. jejuni , as a mutant lacking lipooligosaccharide sialic acid residues showed greater immunoreactivity and decreased serum resistance ( Kreling et al, 2020 ). The CDT complex, another important factor in Campylobacter , codes for the cytolethal distending toxin with cdt B acting as the catalytic site, and in the nucleus, cdt B induces cell cycle arrest and leads to apoptosis of both immune and epithelial cells in the intestines ( Jain et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Campylobacter species also possess other genes associated with adhesion ( cad F and pld A), invasion ( cia B), thermo-tolerance ( dna J) ( Pillay et al, 2020 ), and stress response ( csr A) ( Fields and Thompson, 2008 ). Studies have shown that Campylobacter strain mutants for cad F and cia B exhibited a reduced attachment and invasion of INT 407 cell line along with a decline of survival potential ( Kreling et al, 2020 ; Ramires et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It can be speculated that, as in the case of H. pylori , CDT-vacuolating cytotoxin enables the destruction of intestinal villi and invasion of the intestinal mucosa. Furthermore, CDT toxin leads to DNA damage as demonstrated in mouse models [ 84 ]. It has been demonstrated that cells exposed to CDT-DNA damaging agents suffer extensive genetic modifications that could cause apoptosis; hence, researchers speculate that the human clinical isolate C. jejuni 81–176 is able to promote colorectal cancer [ 85 ].…”
Section: Role Of Bacteria In Gastrointestinal Lymphomamentioning
confidence: 99%
“…Campylobacter is the most commonly reported gastrointestinal bacterial pathogen in humans in the European Union (EU) since 2005, with 220,682 confirmed cases of Campylobacteriosis in 2019 [ 1 ]. Campylobacter spp., in particular Campylobacter jejuni ( C. jejuni ) and Campylobacter coli ( C. coli ), are ubiquitous in nature, and their niche seems to be the intestinal mucosa of warm-blooded hosts [ 2 , 3 ], especially those of avian species. In poultry, the natural bacterial colonization is mainly associated with horizontal transmission at the farm level, and to a lesser extent to vertical transmission [ 4 ], with a mean prevalence in the EU of 71.2% of broiler batches [ 5 ].…”
Section: Introductionmentioning
confidence: 99%